The association between childhood trauma and adolescent cyberbullying: chain mediating roles of emotional intelligence and online social anxiety - Cao, Guanghai; Wei, Xinyu; Liu, Juan; Li, Xianyin (Frontiers in Psychiatry, 2023)
Objective This study explored the impact of childhood trauma on adolescent cyberbullying and the mediating roles of emotional intelligence and online social anxiety between them. Methods The Childhood Trauma Scale, Emotional Intelligence Scale, and Chinese Brief Version of the Social Media User Social Anxiety Scale and Cyber Bullying Scale were used to assess 1,046 adolescents [boys: 297, girls: 749, average age = 15.79 years] from four schools in Shandong Province, China. SPSS 25.0 and AMOS 24.0 were used for statistical analysis. Results (1) Childhood trauma was positively associated with adolescents’ cyberbullying; (2) Emotional intelligence and online social anxiety played partial mediating roles in the relationship between childhood trauma and cyberbullying; (3) Emotional intelligence and online social anxiety played a chain mediating role in the relationship between childhood trauma and cyberbullying. Conclusion This study reveals the relationship and mediating mechanisms between childhood trauma and cyberbullying. It provides implications for the theory and prevention of cyberbullying.